Islam Madzhab Indonesia (Menelisik Karakteristik Bangunan Fiqh Khas Keindonesiaan) - Mustatho Mustatho (STAI Sangatta Kutai Timur, 2020)
Fiqh Keindonesiaan is an effort of the embodiment of Islamic Law with the cultural context and personality of the nation. Fiqh Keindonesiaan meniscaya exist for two reasons, the first time and place of different implementation between Indonesia and other Islamic centers. Secondly, the reason that every place has customs and customs varies according to the socio-anthropological and socio-political tendencies of each place; kaedah which reinforces this reason is